2017
DOI: 10.1007/s10552-017-0982-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to longitudinal adherence in colorectal cancer screening: qualitative research findings

Abstract: Considering the importance of primary healthcare professionals in the decision regarding sustained participation, it is important to better engage them with cancer screening programs, as well as improve the communication channels to provide accurate and balanced information for both health professionals and individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 59 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…The publicity for screening programs in Spanish autonomous communities has led to more general knowledge about the significance of early detection of CRC [11,17,31,34,43,44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The publicity for screening programs in Spanish autonomous communities has led to more general knowledge about the significance of early detection of CRC [11,17,31,34,43,44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…While people seem to dislike automated phone calls [142], video decision aids (DAs) were appreciated by participants interviewed by Brackett et al [143], Coughlin et al [141], and Gwede et al [62], with the latter suggesting that a physician should serve as the narrator. In this regard, many studies reported that suggestions by a physician, particularly if this was the patient's general practitioner, could positively influence screening participation [46,50,52,53,62,[106][107][108]114,133,137,139,144]. For example, participants interviewed by Gordon and Green [114] reported that they would undergo screening "if the doctor told them why it is important for them to get screened".…”
Section: Other Potential Addressing Measures For Increasing Participation In Crc Screeningmentioning
confidence: 99%
“…This indicates that confirmation of good health has a value in itself (57) and may be established as a meaningful narrative with drama and relief, expressed and interpreted in a social context (37,58). It has been suggested that a 'false alarm' might elicit a feeling of being examined for good, triggering a 'relaxation effect', potentially delaying visits to the doctor in case of emerging symptoms or not participating in future screening (19,59). Our study indicated that participants e pe ie es did not hamper intentions for future screening.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, screening also involves risks for 'false alarm' for the individual participant if the FOBT detects blood in the stool, indicating a risk of CRC, and it is followed by a diagnostic colonoscopy which does not detect CRC. This might cause residual uncertainty and distress in some individuals, but results about distress related to CRC screening participation are inconsistent, suggesting no clinically relevant distress in most participants (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Some studies indicate that feelings of trust and moral obligation are drivers of participants' intentions to be screened (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%